Interrogating the Community Participation Paradigm: A theoretical Perspective - Jephias Mapuva (Journal of Research in Social Science and Humanities, 2025)
Community participation in governance processes has been viewed as enhancing a democratic culture within concerned communities by making participants part of the problem-solving mechanism. Proponents of community participation espouse divergent views but concur that positive attributes are realised. In South Africa the post-1994 democratic dispensation has created an enabling environment for community participation at different levels of government. This has been necessitated in part to the participatory approach the communities undertook to dislodge the apartheid regime. In South Africa, through appropriate constitutional provisions, communities have been empowered to have a stake in the running of their own affairs through elected councillors and municipal officials. With community participation, people have felt to be part of a solution to problems in their communities and this has helped to eliminate poverty through the engagement of private sector to provide services which cannot be efficiently delivered by government. Lack of interest in municipal affairs has also resulted in non-participation by some communities.